Coercive Controlling Behaviors and Reporting Physical Intimate Partner Violence in Australian Women: An Exploration. (February 2022) - Patafio, Brittany; Miller, Peter; Walker, Arlene; Coomber, Kerri; Curtis, Ashlee; Karantzas, Gery; Mayshak, Richelle; Taylor, Nicholas; Hyder, Shannon
This study explores two approaches to measuring coercive controlling behaviors (CCBs)—counting how many different CCB types and examining the frequency of each CCB experienced—to examine their utility in explaining the relationship between CCBs and physical intimate partner violence (IPV). Australian women aged 18–68 years ( n = 739; M age = 31.58, SD age = 11.76) completed an online survey. Count and frequency CCB approaches yielded similar significant associations with increased physical IPV. Both approaches suggest that frightening behaviors in particular are significantly indicative of also experiencing physical IPV; however, when you count CCB types, public name-calling becomes important, whereas when you examine the frequency of each CCB type, jealousy/possessiveness becomes important. These findings suggest differential utility between measures of CCBs, which examine the frequency of specific CCB types and which count CCB types, and that both approaches are useful in understanding how coercion and control relate to physical violence within intimate relationships.